Pasantía plan de marketing para la Ortopédica San Carlos del Quindío (2016)
This research is based on doing an internship for Orthopedic San Carlos del Quindío, which was aimed to create and implement a marketing plan for it, focused on certain aspects that allow the company to have a position in the market, covering more customers to departmental level and then, as the ultimate goal, dabble in recognition national and international level. For this work took into account studies external and internal company level, obtaining sectorial data, information providers and other studies to respond efficiently targeted to Quindiano market through work that was developed for recognition and brand positioning for that business.